Best Answer

(n2 + 2n - 1) (n2 + 2n - 1) = n4 + 2n3 - n2 + 2n3 + 4n2 - 2n - n2 - 2n + 1

= n4 + 4n3 + 2n2 - 4n + 1

try with n = 5:

(5 squared + 10 - 1) squared = 34 squared = 1156

with formula

(5^4) + (4 *(5^3)) + (2 * (5^2)) - (4 * 5) + 1

= 625 + 500 + 50 - 20 + 1

= 1156

Q: What is the square of n squared plus 2n minus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

That factors to (2n + 1)(n + 2)

16, 36, 64, 100, 144, 196 etc The square of any even number is a multiple of 4 because an even number is 2n and (2n) squared is 4 (n squared).

4n

7+2n

4n - 2n = 18 Therefore, 2n = 18 Therefore, n = 18/2 = 9

Related questions

n(2n - 1)(2n + 7)

It is: 2n^2 -5n -42 equals (2n+7)(n-6) when factored

It is 2n^3 + 7n^2 - 13n + 3

That factors to (2n + 1)(n + 2)

6n(2n - 3)

m2 - 4mn - 12n2 = m2 - 6mn + 2mn - 12n2 = m(m - 6n) + 2n(m - 6n) = (m + 2n)(m - 6n)

n is 2. To solve, do the division: . . . . . . . . .x2 +. 3x + (6-2n) . . . -------------------------- x-2 | x3 + x2 - 2nx + n2 . . . . .x3 -2x2 . . . . .-------- . . . . . . . .3x2 - 2nx . . . . . . . .3x2 - . 6x . . . . . . . .---------- . . . . . . . . . (6-2n)x + n2 . . . . . . . . . (6-2n)x - 2(6-2n) . . . . . . . . . ---------------------- . . . . . . . . . . . . . . . .n2 + 2(6-2n) But this remainder is known to be 8, so: n2 + 2(6-2n) = 8 ⇒ n2 - 4n + 4 = 0 ⇒ (n - 2)2 = 0 ⇒ n = 2

16, 36, 64, 100, 144, 196 etc The square of any even number is a multiple of 4 because an even number is 2n and (2n) squared is 4 (n squared).

6n2 + 16n can be factorised to give 2n(3n + 8) so the highest factor is 2n.

If the given equation were factorized it would be: 2n2 + 4n = 2n(n+1) Another Answer:- The given expression when factored is 2n(n+2)

5m+2n, n-3m, 7-3n (5m+2n)+(n-3m)+(7-3n)=2m+7

1: (n-2)2 2: n-22 3: n+2n-2 4: n-2n+2 If I understand your question correctly (it is really confusing) then none of the expressions 2 3 or 4 equal the first expression.